Assessment of the quality of recommendations from 161 clinical practice guidelines using the Appraisal of Guidelines for Research and Evaluation–Recommendations Excellence (AGREE-REX) instrument shows there is room for improvement - Ivan D. Florez (Implementation Science, 2020)
Abstract Objective To assess the quality of recommendations from 161 clinical practice guidelines (CPGs) using AGREE-REX-D (Appraisal of Guidelines REsearch and Evaluation-Recommendations Excellence Draft). Design Cross-sectional study Setting International CPG community. Participants Three hundred twenty-two international CPG developers, users, and researchers. Intervention Participants were assigned to appraise one of 161 CPGs selected for the study using the AGREE-REX-D tool Main outcome measures AGREE-REX-D scores of 161 CPGs (7-point scale, maximum 7). Results Recommendations from 161 CPGs were appraised by 322 participants using the AGREE-REX-D. CPGs were developed by 67 different organizations. The total overall average score of the CPG recommendations was 4.23 (standard deviation (SD) = 1.14). AGREE-REX-D items that scored the highest were (mean; SD): evidence (5.51; 1.14), clinical relevance (5.95; SD 0.8), and patients/population relevance (4.87; SD 1.33), while the lowest scores were observed for the policy values (3.44; SD 1.53), local applicability (3,56; SD 1.47), and resources, tools, and capacity (3.49; SD 1.44) items. CPGs developed by government-supported organizations and developed in the UK and Canada had significantly higher recommendation quality scores with the AGREE-REX-D tool (p < 0.05) than their comparators. Conclusions We found that there is significant room for improvement of some CPGs such as the considerations of patient/population values, policy values, local applicability and resources, tools, and capacity. These findings may be considered a baseline upon which to measure future improvements in the quality of CPGs.